Comparative Analysis of Quality of Essential Oil of Wormwood Herb Synanthropic Flora of Voronezh Region - N. A. Dyakova; I. M. Korenskaya; A. I. Slivkin (Разработка и регистрация лекарственных средств)
Introduction. The formation and accumulation of biologically active substances in plants is a complex process associated with a number of environmental factors, including anthropogenic ones. The study of the characteristics of the qualitative composition of essential oil of wormwood grass of bitter different from the ecological point of view of the places of harvesting is relevant.Aim. The aim of this study study of the qualitative composition of essential oil of bitter wormwood grass, harvested in areas of the Voronezh region that are different from an ecological point of view.Materials and methods. In the Voronezh region, 4 points of raw materials procurement were selected, diverse in terms of anthropogenic impact. Isolation of essential oil from the raw materials was carried out according to the method of PS "Wormwood of bitter grass". Component composition of the obtained essential oils was determined using Agilent 7890B GC System (Agilent Technologies, USA) with Agilent 5977A MSD mass selective detector (Agilent Technologies, USA). Data analysis and processing was carried out on the basis of NIST11 databases (from 19.05.2011), MassHunter ver. B.06.00 and NIST MS Search ver. 2.0 software were used.Results and discussion. In a sample of essential oil obtained from reserved raw materials, monoterpene compounds account for more than 82 %, and sesquiterpene compounds – 16.6 %, about 2 % are organic impurities. Intensive biosynthesis of monoterpenes was noted in a sample collected in the area of agricultural fields of the Verkhnekhavsky district, its mass fraction is more than 73 %. In samples of raw materials with anthropogenic load (OJSC "Minudobreniya" and Highway M4), the share of monoterpene compounds is significantly lower (63.7 and 49 %, respectively). The increase in the proportion of sesquiterpene compounds in the last samples of wormwood essential oil may be due to the excessive acidity of the urbanized places of the workpiece. The sesquiterpene compound hamazulene, which stains essential oil blue, is identified in only two samples of gorse grass wormwood harvested along agricultural fields and in M4 tracks, which explains the presence of a blue hue in these oils.Conclusion. The chromato-mass spectrometric analysis of the essential oil of the studied samples of bitter wormwood grass made it possible to identify more than 70 different components in them, while the qualitative composition of the essential oil of the raw materials of different places of the workpiece was significantly different, which may indicate a significant influence of the place of growth of the species and anthropogenic factors on the features of the secondary metabolism of terpene compounds in the plant organism.